Performance analysis of air monitoring system using 433 MHz LoRa module - Mas Haslinda, Mohamad; Abdul Rahim, Muhammad Khairul Naim; Baharudin, Elfarizanis; Mohamed Yunus, Mawarni (Wydawnictwo SIGMA-NOT, 2024)
The escalating air pollution issue has garnered significant public attention in recent years. This pervasive environmental challenge exerts a profound negative impact on living organisms and the ecosystem, posing a substantial threat to human health. Moreover, the existing works in air monitoring systems have a limited range and inability to identify specific pollutants. This issue can be solved by developing a real-time air quality monitoring system using the Internet of Things (IoT) and Long Range (LoRa) wireless technologies. This work addresses these issues through gas sensors and remote data collection. The system has been equipped with notification of AQI levels and types of gasses detected via email and the ThingSpeak platform. This work uses a series of gas sensors, MQ135, MQ7, MQ9 and Honeywell gas sensors, to measure the level of harmful gas such as ammonia, carbon monoxide gas, LPG gas, API, and dust particles. The data from the gas sensors is transmitted via LoRa, controlled by Arduino Nano and NodeMCU ESP8266 Wi-Fi module. Findings demonstrate that the proposed air monitoring system detected a higher AQI concentration, 185 ppm, at the Melaka Sentral parking area during peak hours. This reading is classified as unhealthy conditions for health.